Ketidaksetaraan Gender dalam Konsep Nusyuz pada Hukum Keluarga Islam - Nurainun Maharani; Nabila Khairunnisa; Aviva Riani Puteri Irma; Kurniati (AL-Ikhtiar : Jurnal Studi Islam, 2025)
This article aims to re-examine the concept of nusyuz by placing it within a more egalitarian framework of marital relations through a critical reading of classical fiqh literature, modern fiqh discourse, and the practice of Islamic family law in Indonesia. This study employs a library research method by collecting data from classical fiqh manuals, exegetical works, academic journals, religious court decisions, and positive legal regulations. All materials were analyzed qualitatively using a comparative–interpretive approach to identify how gender bias is constructed within the discourse of nusyuz and how it influences legal reasoning. The findings indicate that classical literature frequently positions nusyuz as a violation attributed primarily to wives, whereas contemporary discourse increasingly asserts that such actions may be committed by either spouse, thereby challenging hierarchical understandings of the marital relationship. An examination of religious court rulings reveals that many judges still rely on textual frameworks that offer limited space for more egalitarian interpretations, although there is an emerging tendency toward approaches more responsive to dynamics of violence and relational inequality. This analysis recommends the development of interpretive models attentive to social context and to principles of reciprocal justice in order to enhance the gender sensitivity of family law practice and reduce inequities arising from rigid normative interpretations. Abstrak. Tulisan ini bertujuan menelusuri kembali konsep nusyuz dengan menempatkannya dalam kerangka relasi suami–istri yang lebih setara, melalui pembacaan kritis terhadap literatur fiqh klasik, fiqh modern, serta praktik hukum keluarga Islam di Indonesia. Penelitian menggunakan metode library research dengan menghimpun data dari kitab-kitab fiqh, karya tafsir, jurnal akademik, putusan pengadilan agama, serta regulasi hukum positif. Seluruh bahan dianalisis secara kualitatif melalui pendekatan komparatif-interpretatif untuk melihat bagaimana bias gender terbentuk dalam wacana nusyuz dan bagaimana ia memengaruhi pertimbangan hukum. Temuan menunjukkan bahwa konsep nusyuz dalam banyak literatur klasik lebih sering diposisikan sebagai pelanggaran yang ditujukan kepada istri, sementara wacana kontemporer mulai menegaskan bahwa tindakan serupa dapat dilakukan kedua belah pihak sehingga relasi rumah tangga tidak lagi dipahami secara hierarkis. Kajian terhadap putusan pengadilan agama mengungkap bahwa sebagian hakim masih mengandalkan kerangka tekstual yang kurang memberi ruang pada pendekatan yang lebih setara, meskipun ada kecenderungan baru yang lebih responsif terhadap dinamika kekerasan dan ketimpangan relasi. Analisis ini merekomendasikan perlunya model pembacaan yang memperhatikan konteks sosial dan prinsip keadilan hubungan timbal balik agar praktik hukum keluarga lebih sensitif terhadap ketidaksetaraan gender yang muncul dari interpretasi normatif yang kaku